The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.4314/jasem.v21i7.18
|View full text |Cite
|
Sign up to set email alerts
|

Adsorptive removal of cationic dye from aqueous solution using chemically modified African Border Tree (<i>Newbouldia laevis</i>) bark

Abstract: This study investigated the biosorption efficiency of sodium hydroxide modified African Border tree (SMABT) bark powder on Safranin O, a cationic dye. The SMABT was characterized by Fourier Transform Infrared Spectroscopy (FTIR). As the initial dye concentration increased, the amount of Safranin O removed increased. The kinetic studies were described by pseudo first order and pseudo second order. The pseudo second order fitted very well into the kinetic experimental data. Freundlich, Langmuir, Temkin and Dubin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…The calculated values of ∆S , ∆H and ∆G are vital thermodynamic parameters in the adsorption process. The intercept and slope of the Van't Hoff plot of ln k against 1/T , as shown in Figure 12, yielded the values of ∆S , ∆H, which were consistent [8]. Table 5 presents the thermodynamic parameters for the adsorption of SO on modified Senna fistula.…”
Section: Thermodynamicssupporting
confidence: 64%
See 1 more Smart Citation
“…The calculated values of ∆S , ∆H and ∆G are vital thermodynamic parameters in the adsorption process. The intercept and slope of the Van't Hoff plot of ln k against 1/T , as shown in Figure 12, yielded the values of ∆S , ∆H, which were consistent [8]. Table 5 presents the thermodynamic parameters for the adsorption of SO on modified Senna fistula.…”
Section: Thermodynamicssupporting
confidence: 64%
“…The use of agricultural waste material (biosorbent) is the cheapest form of adsorbent, for it has zero cost to acquire. Some of the biosorbents used to remove dyes include coconut husk [7] African Border Tree [8], oil palm fruit [9,10], watermelon rinds [11], okra [12], maize stuck, teak leaf [13], sugarcane bargass [14].…”
Section: Introductionmentioning
confidence: 99%
“…Haddad et al [ 63 ] reported the removal of 87% of SO using mussel shells at a concentration of 0.02 g L −1 . Similarly, Ajaelu et al [ 64 ] used Newbouldia laevis tree bark at a concentration of 0.02 g L −1 and obtained a 92% removal rate for SO dye. Thus, the use of okara to remove SO yielded better results than those obtained in previous studies.…”
Section: Resultsmentioning
confidence: 99%
“…Ekka et al [87] studied the efficiency of a silica nanocomposite coated with titanium oxide for the removal of SO and obtained five regeneration cycles. Shariati et al [7] obtained eight regeneration cycles using iron oxide nanoparticles modified with sodium sulphate for [88] Rice husks 178.1 303 K Vasanth Kumar and Sivanesan [74] Beet pulp 147 298 K Malekbala et al [89] Calcined mussel shells 107.8 298 K Haddad et al [63] Border tree (Newbouldia laevis) 90.9 308 K Ajaelu et al [64] Modified red mud 89.4 303 K Sahu et al [90] Activated carbon and rice husks 72.08 308 K Gupta et al [62] Spirulina sp. 54.05 298 K Uyar et al [86] Pineapple peels 21.7 308 K Mahamad et al [91] T A B L E 7 Thermodynamic parameters of methylene blue (MB) and safranin orange (SO).…”
Section: Regeneration Studymentioning
confidence: 99%
“…Numerous investigations have been conducted in this area [40]. Eucalyptus [41,42], flamboyant pod [43], African border [44], pine [45], Sycamore [46], Azollapinnata [47], and many more plant species are among those researched. Plant barks can be used as adsorbents for water treatment because they are inexpensive and have a number of other benefits as well.…”
Section: Introductionmentioning
confidence: 99%